Quality and Consumer Evaluation of Goods On The Market in an Innovation Economy - Mamatkulova Shoira Jalolovna (Scientific Trends, 2024)
In the article we consider the impact of the innovative economy on the quality of goods and consumer assessment. In an ever-changing innovation landscape, businesses are forced to reconsider quality strategies and approaches to consumer perception of innovative products. In the article we analyze the key aspects of product quality that influence their successful implementation in an innovative environment, as well as the methods and criteria that consumers use to evaluate innovative products. Practical recommendations are provided for enterprises seeking to adapt their quality strategies to the dynamics of innovative changes in the market.
Keywords: Innovation economy, product quality, consumer assessment, innovative products, quality strategies, consumer perception, technological innovation, resistance to change, market competition, adaptation to market requirements.